Matematyka
Gienia22
2017-09-25 04:10:27
Rozwiąż równania i sprawdź otrzymane wyniki. a) 2x - 5x = -6 b) 3x + x = 0 c) 3x - 2x = -1/5 d) -x + 2x = -3 e) 4x - x = 9 f) - 1 i 1/3 x - 1/3x = 4 kto pierwszy dobrze odpowie daje naj <3
Odpowiedź
mateusz1122
2017-09-25 05:44:21

a) 2x - 5x = -6  -3x= -6 /:(-3) x= 2 spr. L= 2*2- 5*2= 4-10= -6 P= -6, L=P b) 3x + x = 0 4x= 0 x= 0 spr. L= 3*0+0= 0 P=0, L=P c) 3x - 2x = -1/5 x= -1/5 spr. L= 3*(-1/5) - 2*(-1/5)= -3/5+ 2/5= -1/5 P= -1/5, L=P d) -x + 2x = -3 x= -3 spr. L= -(-3)+2*(-3)= 3-6= -3 P= -3, L=P e) 4x - x = 9 3x= 9 /:3 x=3 spr. L= 4*3-3= 12-3= 9 P= 9, L=P f) - 1 1/3 x - 1/3x = 4 -4/3x- 1/3x = 4  -5/3x= 4 / *3 -5x= 12 /:(-5) x= - 2 2/5 spr. L= -1 1/3 *(-2 2/5) - 1/3*(- 2 2/5)= -4/3 *(- 12/5)- 1/3*(-12/5)= 16/5+4/5= 20/5= 4 P= 4, L=P

Livcia09
2017-09-25 05:45:36

a) 2x-5x=-6 -3x=-6 /:(-3) x=2 spr; 2*2-5*2=-6 4-10=-6 -6=-6 L=P b) 3x+x=0 4x=0 x=0  spr 3*0+0=0 0=0 L=P c) 3x-2x=-1/5 x=-1/5 spr 3*(-1/5)-2*(-1/5)=-1/5 -3/5+2/5=-1/5 -1/5=-1/5 L=P d) -x+2x=-3 x=-3 spt -(-3)+2*(-3)=-3 3-6=-3 -3=-3 L=P e) 4x-x=9 3x=9 /:3 x=3 spr 4*3-3=9 12-3=9 9=9 L=P f) -1 1/3x-1/3x=4 -1 2/3x=4 /:(-1 2/3) x=4*(-3/5)=-12/5 x=-2 2/5 spr -1 1/3*(-2 2/5)-1/3 * (-2 2/5)=4 -4/3*(-12/5)-1/3*(-12/5)=4 48/15+4/5=4 48/15+12/15=4 60/15=4 4=4 L=P

Dodaj swoją odpowiedź